(untitled) (Research, Society and Development, 2022)
The objective of the study was to develop a software that helps in the detection of Burnout Syndrome in health professionals who work in childbirth care at the Maternity Dona Evangelina Rosa (MDER) and provides details of the profile of these professionals, allowing, consequently, to generate projects of intervention and decrease its prevalence. A methodological study was carried out with a quantitative approach in order to develop software to assist in the diagnosis of Burnout Syndrome in the period of June and July 2021. Data were collected by the software and exported, being examined in the SPSS version 20.0 program. The software presents information from 6 dimensions developed from knowledge about childbirth care through legislation of the unified health system, related to pregnant women and professionals who provide childbirth care, as well as literature on Burnout Syndrome and its repercussions. on the relationship between pregnant women and health professionals. The content validation of all dimensions had a Content Validity Index above 80%, demonstrating the experts’ agreement in relation to the software’s information. The study made it possible to develop mobile software with secure information that serves as a strategy in the diagnosis of Burnout Syndrome in health professionals who provide childbirth care, serving the manager as a tool in the prevention of negative outcomes for mother and fetus.